CULTURE RESEARCH IN THE RECENT WORK OF ITAMAR EVEN-ZOHAR - Harry Aveling (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
Even-Zohar is highly regarded among scholars of Translation Studies for his theoretical contributions in the area of "Polysystem Theory". This paper presents an introduction to EvenZohar's more recent work in the area of"cuIture research" (which he distinguishes from Cultural Studies). It locates his thinking within a framework deriving from Russian Formalism and, more recently, Russian Semiotics. The major focus in his Papers in Culture Research (200412005) is on culture as a socio-semiotic system, allowing for both reflection and action. A significant term in discussing systems is "repertoire", the rules and materials which govern the production and use of given cultural objects. Even-Zohar's papers seek to place repertoire within a broader framework, and to allow for the invention and transfer of repertoires between various social groups. The work of idea-makers is particularly important in this transfer. Tile paper concludes with a consideration of the relevance of "culture research" to Translation Studies. It suggests that his ideas are of limited use but may provide the basis for further reflection on the roles of translators and translations, especially in new nation states.